Experimental Investigation on Rotordynamic Characteristics and Rotor System Stability of a Novel Negative Dislocated Seal. (17th June 2019) - Sun, Dan; Wang, Xudong; Fei, Chengwei; Zhao, Huan; Zhang, Guochen; Tang, Wenzhong
Abstract : Air-induced force generated in seals is one key factor on the stability of the rotor system. In this paper, a novel negative dislocated seal (NDS) was developed in respect of dislocated bearing theory, to reduce hydrodynamic pressure effect and air-induced force and improve rotor stability as well. A test rig was built to test rotordynamic characteristics and rotor stability of the NDS. The rotordynamic characteristics of seals were investigated based on the unbalanced synchronous excitation method, and seal-rotor system stability was evaluated by the identification method with an electromagnetic bearing exciter. The effects of both rotating speed and inlet/outlet pressure ratio on the rotordynamic characteristics and rotor stability of both NDS and conventional cylindrical labyrinth seal were experimentally investigated. The results show that with the increasing rotating speed, inlet/outlet pressure ratio is promising to reduce the direct stiffness coefficients of seals and the logarithmic decrement rate of seal-rotor system and enhance both cross stiffness and damping coefficient as well. Besides, the developed NDS effectively reduces cross-stiffness coefficients and increases direct damping coefficients and the logarithmic decrement rate of the seal-rotor system, relative to the conventional cylindrical seal. The proposed seal can effectively improve seal stability of turbomachinery.